Co-administration of Shexiang Baoxin Pill and Chemotherapy Drugs Potentiated Cancer Therapy by Vascular-Promoting Strategy - Yang, Liu-qing; Li, Ru-yi; Yang, Xi-yan; Cui, Qian-fei; Wang, Fei-yun; Lin, Guo-qiang; Zhang, Jian-ge (Frontiers in Pharmacology, 2019)
Effective delivery of chemotherapeutic agents to tumors is a critical objective of improved cancer therapy. Traditional antiangiogenic therapy aims at eradicating tumor blood vessels, but the subsequently reduced blood perfusion may limit the drug amount delivered into the tumor and potentially lead to tumor hypoxia, which has been proved to be unable to meet the therapeutic expectations. ‘Shexiang Baoxin Pill’ (SBP) is a well-known traditional Chinese medicine (TCM) used in clinical treatment of cardiovascular diseases, which has the pharmacological effect of pro-angiogenesis demonstrated recently. In this study, we disclosed our finding that SBP could enhance the effective treatment performance of gemcitabine (GEM) while minimizing the toxic side effects caused by GEM. Mechanistically, SBP increased tumor angiogenesis, blood perfusion, vascular permeability and vessel dilation, which subsequently favored the delivery of GEM to the tumor lesion. Moreover, combined treatment with SBP and GEM could modify tumor microenvironment and consequently overcome multidrug resistance, and this combination therapy is also suitable for combination of SBP with some other chemotherapeutic drugs as well. These results suggest that combining SBP with chemotherapeutic agents achieves better treatment efficiency, which can open an avenue for expanding the combined treatment of anti-cancer chemotherapeutic drugs with TCM.